Blood Pressure and Body Composition During First Year of Antiretroviral Therapy in People With HIV Compared With HIV-Uninfected Community Controls. (26th July 2022) - Kavishe, Bazil Baltazar; Olsen, Mette Frahm; Filteau, Suzanne; Kitilya, Brenda W; Jeremiah, Kidola; Krogh-Madsen, Rikke; Todd, Jim; Friis, Henrik; Faurholt-Jepsen, Daniel; PrayGod, George; Peck, Robert
Abstract: Background: Body composition changes may explain the rapid increase in blood pressure (BP) in people with HIV (PWH) during the first year of antiretroviral therapy. Methods: We analyzed data from a cohort of PWH and HIV-uninfected adults from the same communities in Mwanza, Tanzania. Blood pressure (BP, mm Hg) and body composition data were collected at baseline and 12-month follow-up. We used multivariable linear regression to compare BP changes in PWH and HIV-uninfected adults, and the relationship between changes in body composition and changes in BP. Results: BP data were available for 640 PWH and 299 HIV-uninfected adults. Sixty-four percent were women and the mean age was 38 years. In PWH, systolic BP (SBP) increased (114–118) whereas SBP decreased (125–123) in HIV-uninfected participants. Fat mass increased by 1.6 kg on average in PWH and was strongly associated with the change in BP ( P < 0.001). The greater increase in SBP in PWH was partly explained by the lower baseline SBP but PWH still experienced a 2.2 (95% CI: 0.3–4.2) greater increase in SBP after adjustment. Weight gain partially mediated the relationship between HIV and SBP increase in PWH; a 1-kg increase in fat mass accounted for 0.8 (95% CI: 0.6–1.1) increase in SBP. Conclusions: Weight and fat mass increase rapidly in PWH during the first 12 months of antiretroviral therapy and contribute to a rapid increase in SBP. Interventions to prevent excessive increase in fat mass are needed for PWH. Graphical Abstract: